Membrane Deformation under Local pH Gradient: Mimicking Mitochondrial Cristae Dynamics - Khalifat, Nada (The Biophysical Society, 2008)
Mitochondria are cell substructures (organelles) critical for cell life, because biological fuel production, the ATP synthesis by oxidative phosphorylation, occurs in them driven by acidity (pH) gradients. Mitochondria play a key role as well in the cell death and in various fatigue and exercise intolerance syndromes. It is clear now that mitochondria present an astonishing variety of inner membrane morphologies, dynamically correlated with their functional state, coupled with the rate of the ATP synthesis, and characteristic for normal as well as for pathological cases. Our work offers some original insights into the factors that determine the dynamical tubular structures of the inner membrane cristae. We show the possibility to induce, by localized proton flow, a macroscopic cristae-like shape remodeling of an only-lipid membrane. We designed a minimal membrane system (GUV) and experimentally showed that the directional modulation of local pH gradient at membrane level of cardiolipin-containing vesicles induces dynamic cristae-like membrane invaginations. We propose a mechanism and theoretical model to explain the observed tubular membrane morphology and suggest the underlying role of cardiolipin. Our results support the hypothesis of localized bioenergetic transduction and contribute to showing the inherent capacity of cristae morphology to become self-maintaining and to optimize the ATP synthesis.